Ebolavirus Replication and Tetherin/BST-2 - Yasuda, Jiro (Frontiers in Microbiology, 2012)
Ebolavirus (EBOV) is an enveloped, non-segmented, negative-stranded RNA virus, which consists of five species: Zaire ebolavirus, Sudan ebolavirus, Tai Forest ebolavirus, Bundibugyo ebolavirus, and Reston ebolavirus. EBOV causes a lethal hemorrhagic fever in both humans and non-human primates. The EBOV RNA genome encodes seven viral proteins: NP, VP35, VP40, GP, VP30, VP24, and L. VP40 is a matrix protein and is essential for virus assembly and release from host cells. Expression of VP40 in mammalian cells is sufficient to generate extracellular virus-like particles, which resemble authentic virions. Tetherin/BST-2, which was identified as an effective cellular factor that prevents human immunodeficiency virus-1 release in the absence of viral accessory protein Vpu, has been reported to inhibit ZEBOV VP40-induced VLP release. Tetherin/BST-2 appears to inhibit virus release by physically tethering viral particles to the cell surface via its N-terminal transmembrane domain and C-terminal glycosylphosphatidylinositol anchor. Replication of ZEBOV is not inhibited by tetherin/BST-2 expression, although tetherin/BST-2 was expected to inhibit EBOV release as well as VLP release. Recently, it was reported that viral glycoprotein of EBOV, GP, antagonizes the antiviral effect of tetherin/BST-2. However, the mechanism by which GP antagonizes the antiviral activity of tetherin/BST-2 and whether GP of the other EBOV species function as antagonists of tetherin/BST-2 remain unclear.